The Development of Comparative Linguistics in the Pre-Independence Period of Uzbekistan - Mahkamova Shahlo (International Journal on Integrated Education, 2022)
This article deals with the issues based on analyzing the development of comparative linguistics in the pre-independence period of Uzbekistan. The possibilities and necessity of using a contrastive approach in teaching foreign language teachers in modern conditions are described. Comparison of languages is one of the most important methods for studying bilingualism, which is especially important in the conditions of our country, an effective method for studying the interaction and mutual enrichment of languages. As well as, it can create a universal model or a universal metalanguage, with the help of which it is possible to establish the degree of proximity of languages, their similarities and differences, it can also provide general linguistics with new data.